Neurocognitive deficits are relevant for the jumping-to-conclusions bias, but not for delusions: A longitudinal study - Andreou, Christina (Schizophr Res Cogn, 2015)
Patients with delusions exhibit an increased tendency to arrive at decisions based on very limited evidence (jumping-to-conclusions; JTC), making this reasoning bias relevant for the treatment of delusions. Neurocognitive deficits contribute to JTC, but it is not known whether this has any bearing on the clinical syndrome of delusions. We addressed this question by reanalyzing data from an efficacy study of non-pharmacological interventions as adjunctive treatments in schizophrenia. We investigated the longitudinal associations of cognitive functioning, JTC and delusions in patients with psychotic disorders receiving either a metacognitive intervention addressing reasoning biases (n = 59), or cognitive remediation (n = 58). Both interventions improved JTC; in the cognitive remediation group, tentative evidence suggested that better neurocognitive performance contributed to this improvement. However, JTC gains were associated with delusion improvement only in the metacognitive intervention group, suggesting a content-specific mechanism of action.